2004
DOI: 10.14411/fp.2004.043
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Dracunculus globocephalus Mackin, 1927 (Nematoda: Dracunculidae), a parasite of the snapping turtle, Chelydra serpentina

Abstract: Abstract. Dracunculus globocephalus Mackin, 1927 (Nematoda: Dracunculoidea) is redescribed from specimens collected from the mesentery of the snapping turtle, Chelydra serpentina (L.), in Louisiana, USA. The use of scanning electron microscopy, applied for the first time in this species, made it possible to study details in the structure of the cephalic end and the arrangement of male caudal papillae that are difficult to observe under the light microscope. This species markedly differs from all other species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Even in the study of the dracunculid parasites that are never found in humans or other mammals, the molecular approach used in the present study may still be useful, negating the need for more complex and more labourintensive morphology based on light or electron microscopy (Moravec and Little, 2004). A nematode from the Ugandan DEP, recently received at the CDC, could not be identified as D. medinensis by light microscopy, and sequence analysis of the extracted and amplified DNA confirmed that the specimen was not Dracunculus (unpubl.…”
Section: Discussionmentioning
confidence: 98%
“…Even in the study of the dracunculid parasites that are never found in humans or other mammals, the molecular approach used in the present study may still be useful, negating the need for more complex and more labourintensive morphology based on light or electron microscopy (Moravec and Little, 2004). A nematode from the Ugandan DEP, recently received at the CDC, could not be identified as D. medinensis by light microscopy, and sequence analysis of the extracted and amplified DNA confirmed that the specimen was not Dracunculus (unpubl.…”
Section: Discussionmentioning
confidence: 98%
“…Mirza (1957) subsequently suggested, from studies showing variations in morphology within a single species, that all specimens described from reptiles belonged to the same species. However, a redescription of D. globocephalus by Moravec and Little (2004) showed this species to be clearly different from D. ophidensis. The close similarity between species, including between those infecting mammals and those infecting reptiles, has been commented upon frequently (Yorke & Maplestone, 1926;Desportes, 1938;Moorthy, 1937;Muller, 1971;Moravec & Little, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…However, a redescription of D. globocephalus by Moravec and Little (2004) showed this species to be clearly different from D. ophidensis. The close similarity between species, including between those infecting mammals and those infecting reptiles, has been commented upon frequently (Yorke & Maplestone, 1926;Desportes, 1938;Moorthy, 1937;Muller, 1971;Moravec & Little, 2004). Recently, ribosomal RNA analysis (Wijová , Moravec, Horá k, Modrý , & Lukeš, 2005) demonstrated conclusively that D. oesophageus from colubrid snakes and the morphologically similar D. medinensis (Linnaeus, 1758) from humans are distinct species.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…from non-human hosts may well concern D. medinensis. Moreover, the validity of the other 11 nominal species of the genus Dracunculus, all histozoic parasites of mammals and reptiles, is frequently questioned because of their inadequate descriptions and/or morphological similarity (Mirza 1957;Muller 1971;Moravec and Little 2004). However, the 18S rRNA sequences presented herein show beyond any doubt that the dracunculid Fig.…”
mentioning
confidence: 80%